Analysis of Public Service Standards for Inpatient Care at Dumai City Regional General Hospital (RSUD) - Dede Mirza; Lilis Wahyuni; Fitra Hadi Khaz; Yuliana Yuliana (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to evaluate the implementation of Public Service Standards in inpatient services at Dumai City Regional General Hospital (RSUD) as an important part of the provision of health services to the community. Public service standards are needed to ensure service quality, efficiency, transparency, and public satisfaction as service users. However, in practice, various problems are still found, particularly related to the timeliness of service, clarity of service costs, and the availability of supporting facilities and infrastructure. This study uses a qualitative descriptive approach with research subjects including hospital management, inpatient service staff, and community service users. Data collection was conducted through in-depth interviews, direct observation, and documentation studies to obtain a comprehensive picture of the implementation of public service standards. The data obtained were analyzed using thematic analysis methods through the stages of data transcription, coding, theme identification, theme grouping, and data interpretation. The results of the study indicate that the overall implementation of Public Service Standards in inpatient care at Dumai City Regional General Hospital is in the good category. Indicators of service procedures, service products, and the competence of service providers have been implemented quite optimally, characterized by clear procedures, services that meet patient needs, and friendly and professional staff attitudes. However, the service completion time and cost indicators are still in the fairly good category, which indicates delays in service and limited information regarding costs received by patients. Furthermore, facilities and infrastructure are the indicators that require the most attention, especially regarding the comfort of the waiting room and the completeness of service support equipment. In conclusion, although the standard of public service at the Dumai City Regional Hospital inpatient has been running well, continuous improvement efforts are needed to increase service time efficiency, cost transparency, and the provision of facilities and infrastructure to increase public satisfaction and trust in health services.